De normalistas a normalizadoras : a prática do estágio profissional e suas estratégias e táticas de governo em sala de aula - Amaral, Michele Pedroso do (2020)
This thesis puts into analysis, some of the strategies and tactics used by normalist students, for the organization of their practices during the period of Professional Internship, in the Ordinary Course, in the classroom. The main objectives of this thesis were those of knowing and understanding the pedagogical discourses to which these strategies and tactics historicizing them. To this end, we try to take into account the central idea that interns learn to normalize their ways of being a teacher, in the process of being able to exercise the government in the classroom. The research was developed, in one in a qualitative approach, using the Focal Group as a technique. It was held in two Schools belonging to the Public Educational System of the State of Rio Grande do Sul, with the participation of three interns in each Institution. Authors and authors such as: Foucault (2002; 1987; 2014a; 2003; 2014b; 2014c; 2015; 1999; 2010; 1995; 1989); Nietzsche (2008; 2013); Dussel e Caruso (2003); Veiga (2007); Pineau (2011; 2012), are the main theoretical references of this study. The investigation is not intended to exhaust such a theme, nor even present supposed truths about the issue, but to signal and problematize some ways in which, more comprehensively, the government in the classroom was exercised by normalists, through these strategies and tactics, which are looked at, from: organization of the classroom space and the bodies of children; planning, routine, control of the conducts, and their possible developments.